Endoscopic lateral neck dissection via the breast and transoral approaches for papillary thyroid carcinoma: A preliminary report - Penghao Kuang; Yuanyuan Wang; Guoyang Wu; Yezhe Luo; Jinbo Fu; Wei Yan; Suqiong Lin; Xiaoquan Hong; Fusheng Lin; Ende Lin; Yilong Fu (Frontiers in Surgery, 2022)
PurposeComplete lymph node dissection is essential for the management of papillary thyroid carcinoma (PTC) with lymph node metastasis (LNM). This work aimed to describe the feasibility of endoscopic lateral neck dissection via the breast and transoral approach (ELNDBTOA) in PTC patients and the necessity of the addition of the transoral approach.MethodsWe included 13 patients with PTC and suspected lateral LNM who underwent ELNDBTOA at the Zhongshan Hospital, Xiamen University. Total thyroidectomy, ipsilateral central lymph node dissection, and selective neck dissection (levels IIA, IIB, III, and IV) were performed endoscopically via the breast approach. Residual lymph nodes were further dissected via the transoral approach.ResultsThe mean operation time was 362.1 ± 73.5 min. In the lateral neck compartments, the mean number of retrieved lymph nodes was 36.6 ± 23.8, and the mean number of positive lymph nodes was 6.8 ± 4.7. In further dissection via the transoral approach, lymph nodes in the lateral neck compartment were obtained in nine patients (9/13, 69.2%), and three patients (3/13, 23.1%) had confirmed lateral neck metastases. Transient hypocalcemia occurred in two patients (2/13, 15.4%), and three patients (3/13, 23.1%) developed transient skin numbness in the mandibular area. No other major complications were observed. There was no evidence of local recurrence or distant metastasis during the follow-up period (range, 24–87 months). All patients were satisfied with the good cosmetic outcome.ConclusionELNDBTOA is an option with proven feasibility for select PTC patients with LNM, and the addition of the transoral approach is necessary to ensure complete dissection.